2015
DOI: 10.1038/nm.3843
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological targeting of actin-dependent dynamin oligomerization ameliorates chronic kidney disease in diverse animal models

Abstract: Dysregulation of the actin cytoskeleton in podocytes represents a common pathway in the pathogenesis of proteinuria across a spectrum of chronic kidney diseases (CKD). The GTPase dynamin has been implicated in the maintenance of cellular architecture in podocytes through its direct interaction with actin. Furthermore, the propensity of dynamin to oligomerize into higher-order structures in an actin-dependent manner and to crosslink actin microfilaments into higher order structures have been correlated with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
117
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 106 publications
(126 citation statements)
references
References 55 publications
9
117
0
Order By: Relevance
“…A very recent study could demonstrate that stabilization of the actin cytoskeleton via application of a small molecule affecting the DYNAMIN structure resulted in prevention of progressive proteinuria in a series of genetic and toxic podocyte stress models. These observations underlined the importance of the actin cytoskeleton as a common final pathway of podocyte injury (44,45). Our data now extend these observations and identify with EPB41L5, a podocyte-specific upstream link from the adhesion machinery to the regulation of the cytoskeleton.…”
Section: Discussionsupporting
confidence: 83%
“…A very recent study could demonstrate that stabilization of the actin cytoskeleton via application of a small molecule affecting the DYNAMIN structure resulted in prevention of progressive proteinuria in a series of genetic and toxic podocyte stress models. These observations underlined the importance of the actin cytoskeleton as a common final pathway of podocyte injury (44,45). Our data now extend these observations and identify with EPB41L5, a podocyte-specific upstream link from the adhesion machinery to the regulation of the cytoskeleton.…”
Section: Discussionsupporting
confidence: 83%
“…The slit diaphragm is composed of cell adhesion molecules that are connected to the actin cytoskeleton and its associated proteins (including synaptopodin, vinculin, and dynamin). These changes in podocyte phenotype are closely correlated with a loss of function in glomerular permeability and the characteristic clinical hallmark of proteinuria that occurs in FSGS; for example, the large GTPase dynamin, which plays a key role in the maintenance of kidney barrier filtration, is implicated in regulating the actin cytoskeleton via direct dynamin-actin interactions 8,9 and regulates focal adhesion maturation in podocytes via a parallel signaling pathway to RhoA. 10 Moreover, Notch signaling, which is implicated in the development of glomerular disease, 11 promotes dynamin-dependent, raftindependent endocytosis of nephrin.…”
Section: Epidemiology and Clinical Presentationmentioning
confidence: 99%
“…It has been suggested that an assembly mode that involves many low-affinity interactions sites facilitates the reversibility of interactions and allows for the regulation of dynamin oligomerization, for example through nucleotide binding, hydrolysis or phosphorylation. Our recent study suggests that dynamin assembly presents an ideal pharmacological target as a proxy to target actin cytoskeleton dynamics (39). Another characteristic that distinguishes dynamin from canonical small GTPases is that dynamin directly binds actin filaments (10,40).…”
Section: Actin Cytoskeleton Dynamics As a Pharmacological Target In Kmentioning
confidence: 99%